Achieving Disability Equality: Empowering Disabled People to Take the Lead - Löve, Laufey; Rannveig Traustadóttir 1950-; Rice, James G. (2018)
Achieving disability equality calls for transformative changes to society’s structures and norms. Recognizing the central role of disabled people and their organizations in this restructuring, and the call of the Convention on the Rights of Persons with Disabilities (CRPD) for their full inclusion in all legal and policy decisions relating to their rights, this article focuses on how disability groups and organizations regard their ability to effect changes in line with the CRPD. The article draws on qualitative interviews with leaders of disability organizations and activist groups in Iceland in 2016 and 2017. The findings reflect frustration among the leaders with what they perceive to be a lack of sustained progress in the decade since the country signed the CRPD. In their view, this period has been characterized by a lack of meaningful involvement of disabled people in policymaking, and a lack of political will and interest in disability affairs, which has resulted in stagnation. As a result, leaders of disabled people’s organizations have begun to change their strategies and are taking steps to redefine their approaches, and reframe the issues and dialogue with authorities in a more progressive manner, demanding to have more say in the process of change.
Keywords: CRPD; activist groups; disability equality; disabled people; Empowerment; Policymaking; umbrella organizations